Hydrogen-Induced Micro-Strain Evolution in Super Duplex Stainless Steel—Correlative High-Energy X-Ray Diffraction, Electron Backscattered Diffraction, and Digital Image Correlation - Örnek, Cem; Müller, Timo; Şeşen, Bilgehan M.; Kivisäkk, Ulf; Zhang, Fan; Långberg, Marie; Lienert, Ulrich; Jeromin, Arno; Keller, Thomas F.; Lundgren, Edvin; Pan, Jinshan (Frontiers in Materials, 2022)
The local lattice strain evolution during electrochemical hydrogen charging and mechanical loading in 25Cr-7Ni super duplex stainless steel were measured in-situ using synchrotron high-energy x-ray diffraction. Post-mortem electron backscattered diffraction analysis showed that the austenite phase underwent plastic deformation in the near-surface due to hydrogen-enhanced localized plasticity, where the ferrite phase experienced hardening. In bulk regions, the ferrite was the softer phase, and the austenite remained stiff. Digital image correlation of micrographs recorded, in-situ, during mechanical tensile testing revealed intensified plastic strain localization in the austenite phase, which eventually led to crack initiation. The absorption of hydrogen caused strain localization to occur primarily in austenite grains.